2012
DOI: 10.1037/a0029168
|View full text |Cite
|
Sign up to set email alerts
|

Who becomes an entrepreneur? Early life experiences as predictors of entrepreneurship.

Abstract: Taking a longitudinal perspective, we tested a developmental-contextual model of entrepreneurship in a nationally representative sample. Following the lives of 6,116 young people in the 1970 British Birth Cohort from birth to age 34, we examined the role of socioeconomic background, parental role models, academic ability, social skills, and self-concepts as well as entrepreneurial intention expressed during adolescence as predictors of entrepreneurship by age 34. Entrepreneurship was defined by employment stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
4
20

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 33 publications
8
116
4
20
Order By: Relevance
“…Schoon and Duckworth's (2012) longitudinal study involving over 6,000 individuals tracked from birth until age 34 revealed that becoming an entrepreneur was associated with entrepreneurial career intent expressed at mid-adolescence (age 16). It will be important for future studies to monitor if youth who undergo training end up establishing their own business ventures at some point in their lifetime.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Schoon and Duckworth's (2012) longitudinal study involving over 6,000 individuals tracked from birth until age 34 revealed that becoming an entrepreneur was associated with entrepreneurial career intent expressed at mid-adolescence (age 16). It will be important for future studies to monitor if youth who undergo training end up establishing their own business ventures at some point in their lifetime.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This combination is referred to as entrepreneurial personality (Zhao, Seibert, & Lumpkin, 2010). These personality traits are stable over time and often already displayed at a young age (Obschonka, Duckworth, Silbereisen, & Schoon, 2012;Obschonka et al, 2010;Schoon & Duckworth, 2010). Personality traits have also been linked to success as an entrepreneur (Ciavarella et al, 2004;Owens et al, 2012).…”
Section: Personalitymentioning
confidence: 99%
“…In the empirical literature is a broad consensus that entrepreneurs have a more aggressive, forward (future) oriented, and extrovert personality (e.g., Schoon & Duckworth, 2010;Stuard & Abetti, 1990;White et al, 2006). Entrepreneurs are better able to tolerate ambiguous situations and uncertainty (e.g., Lüthje & Franke, 2003;White et al, 2006) and they tend to be less comfortable with authority and therefore tend to favor autonomy (e.g., Owens, Kirwan, Lounsbury, Levy, & Gibson, 2012).…”
Section: Personalitymentioning
confidence: 99%
See 2 more Smart Citations